PENGARUH PENGGUNAAN MEDIA BELAJAR GADGET TERHADAP HASIL BELAJAR MATEMATIKAPADA SISWA KELAS IV SD NEGERI KOTA MAKASSAR - Sri Wahyuni; Bellona Mardhatillah Sabillah; Eka Fitriana HS; Satriawati Satriawati (Universitas Muhammadiyah Makassar, 2022)
This study aims to determinetheeffect of using gadget learning media on mathematics learning outcomes for fourth graders at Kassi Elementary School in Makassar. This research is experimental research using a quantitativeappriach method. This is experimental research is classified in a pre-experimental form of a one group pretest-posttest design. The sampling technique was 27 students. The research instruments are documentation, tests, observations,and data analysis techniques used in descriptive and inferential statistical analysis. Class IV B as the experimental class will be given a pretest and post-test gadget in this study. The data analysis technique using t-test states that the results of the calculation of the hypothesis test on the post-test data obtained a value of 0,000 which is smaller than the significant rate of 0,05, which means that there is an effect gadget learning media on mathematics learning outcomes. Thus H1 is accepted, and H0 is rejected. So it can be concluded that there is an effect of using gadget learning media on mathematics learning outcomes in fourth-grade students at Kassi Elementary School in Makassar.